Reassembling the Paleogene?Eocene North Atlantic igneous province: New paleomagnetic constraints from the Isle of Mull, Scotland - Ganerød, Morgan; Smethurst, Mark A.; Rousse, Sonia; Torsvik, Trond H.; Prestvik, Tore (Earth and Planetary Science Letters, 2008)
International audience The paleomagnetic data sets from the British Tertiary Igneous Province (BTIP) have recently been criticized as being unreliable and discordant with data from elsewhere in the North Atlantic Igneous Province (NAIP) [Riisager et al. Earth Planet. Sci. Lett. 201 (2002) 261?276; Riisager et al. Earth Planet. Sci. Lett. 214 (2003) 409?425]. We offer new paleomagnetic data for the extensive lava flow sequence on the Isle of Mull, Scotland, and can confirm the paleomagnetic pole positions emanating from important earlier studies. Our new north paleomagnetic pole position for Eurasia at 59 ± 0.2 Ma has latitude 73.3°N, longitude 166.2°E (dp/dm = 5.2/7.0). A re-evaluation and an inter-comparison of the paleomagnetic database emanating from the NAIP were carried out to test for sub-province consistency. We find a general agreement between the Eurasian part of NAIP (BTIP and Faeroes) and East Greenland data. However a compilation of West Greenland data displays a large and unexplained dispersion. We speculate on if this is related to different sense of block rotation of the Tertiary West Greenland constituents. Combining all data from the NAIP constituents, give a pole position at 75.0°N, 169.9°E (N = 25, K = 84.3, A95 = 3.2) in Eurasian reference frame.